2020
DOI: 10.1038/s41419-020-2285-7
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein fragments trigger distinct aggregation pathways

Abstract: Aggregation of alpha-synuclein (αSyn) is a crucial event underlying the pathophysiology of synucleinopathies. The existence of various intracellular and extracellular αSyn species, including cleaved αSyn, complicates the quest for an appropriate therapeutic target. Hence, to develop efficient disease-modifying strategies, it is fundamental to achieve a deeper understanding of the relevant spreading and toxic αSyn species. Here, we describe comparative and proof-ofprinciple approaches to determine the involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…Silencing of the two most upregulated genes CCND1 and CCND2 , involved in the G0/G1 cell cycle initiation, revealed that siRNA against CCND1 alone and in combination with CCND2 markedly reduced cytotoxicity levels. Taken together, early-stage intracellular accumulation of αSyn in human mesencephalic post-mitotic neurons ( Chakroun et al, 2020 ) is accompanied by an altered expression of miRNAs, leading to an enrichment of G0/G1 cell cycle genes. Among them, CCND1 seems to be functionally involved in αSyn-mediated cell death, as shown by siRNA-mediated intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing of the two most upregulated genes CCND1 and CCND2 , involved in the G0/G1 cell cycle initiation, revealed that siRNA against CCND1 alone and in combination with CCND2 markedly reduced cytotoxicity levels. Taken together, early-stage intracellular accumulation of αSyn in human mesencephalic post-mitotic neurons ( Chakroun et al, 2020 ) is accompanied by an altered expression of miRNAs, leading to an enrichment of G0/G1 cell cycle genes. Among them, CCND1 seems to be functionally involved in αSyn-mediated cell death, as shown by siRNA-mediated intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviral SNCA overexpression results in increased intracellular αSyn protein levels and ∼ 50% cytotoxicity levels at day 6 post transduction in differentiated LUHMES neurons ( Höllerhage et al, 2014 ; Chakroun et al, 2020 ). In the present study, we performed a miRNome-wide screen in SNCA -overexpressing LUHMES neurons at day 4 post transduction and focused on (1) altered levels of miRNAs and their target genes and (2) identifying a functional involvement of dysregulated biological pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the relevance of aSyn fragments in the extracellular space was shown not only for spreading but also for aggregation and the formation of different strains. These fragments are also able to mediate the aggregation of endogenous full-length aSyn [ 155 ].…”
Section: Lewy Pathology: More Than Simply One Mechanism or Hypothementioning
confidence: 99%
“…The role of α-syn misfolding in the initiation of PD is well established (Mahul-Mellier et al, 2020). Several studies report on targeting α-syn aggregation and synthesis as a potential therapeutic option in PD (Fields et al, 2019;Chakroun et al, 2020;Gabr and Peccati, 2020;Mahul-Mellier et al, 2020;Ryan et al, 2020). Here, it is important to mention that native α-syn plays a crucial role in releasing the neurotransmitter associated with SV due to its greater curvature, but its over-expression is reported to inhibit the release of neurotransmitters (Sulzer and Edwards, 2019;Cai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%